PREVALENCE OF ORAL CANDIDIASIS IN ORAL LEUKOPLAKIA IN PATIENTS REPORTED IN PRIVATE DENTAL INSTITUTION: A RETROSPECTIVE STUDY - Hafeez, Nauma; Uma Maheshwari, T. N. (International Journal of Psychosocial Rehabilitation, 2020)
Aim: To assess the prevalence of candidiasis in oral leukoplakia in patients reporting to Saveetha Dental College.Background: Candidiasis is an opportunistic infection caused by the Candida albicans species. It occurs when there is an imbalance in the microbiome, resulting in excessive growth of the species and causing white scrapable lesions. The study thus aims at assessing its prevalence in oral leukoplakia cases.Materials and Methods: The study was conducted from June 2019 to March 2020 at Saveetha Dental College amongst a sample size of 97 patients between the ages of 21 and 18 years, of which 92 male and 5 female patients diagnosed as leukoplakia were included in the study. The hospital database was used to retrieve data, and tabulation of the data was done using Excel sheets. Statistical analysis was done using SPSS software. A descriptive frequency test and inferential statistics were done using the Chi square test, and a p value of < 0.05 was considered statistically significant.Results: The study reveals the prevalence of oral candidiasis in oral leukoplakia. The majority of candidiasis and oral leukoplakia occurs in the age group of 31 to 50 years, and males are found to be more affected than females.Conclusion: The prevalence rate agrees with other studies done on candidiasis and leukoplakia; being conscious of the prevalence rate helps in better diagnosis and identification of dysplastic conditions in potentially malignant disorders, as it is proved in earlier studies that candidal invasion is common in malignant changes.